Nuclear Progesterone Receptor Expressed by the Cortical Thymic Epithelial Cells Dictates Thymus Involution in Murine Pregnancy - Ahn, Soo Hyun; Nguyen, Sean L.; Kim, Tae Hoon; Jeong, Jae-Wook; Arora, Ripla; Lydon, John P.; Petroff, Margaret G. (Frontiers in Endocrinology, 2022)
Progesterone is a gonadal pro-gestational hormone that is absolutely necessary for the success of pregnancy. Most notable actions of progesterone are observed in the female reproductive organs, the uterus and the ovary. Acting through the nuclear progesterone receptor (PGR), progesterone prepares the endometrium for the embryo implantation. Interestingly, the maternal thymus also is a known expressor of Pgr; its absence seemed to cause murine pregnancy complications. However, the location and its functional importance were not known. Here, we used transgenic dual fluorescent reporter mouse model and genetic deletion of Pgr in the Foxn1+ thymic epithelial cells (TEC) to demonstrate TEC-specific Pgr expression in pregnancy, especially in the cortex where thymocyte maturation occurs. Using our TEC-specific Pgr knock out mouse model, we demonstrate that TEC-specific Pgr is necessary for pregnancy-induced thymic involution in pregnancy. Our investigation revealed the functional importance of Pgr in thymus involution during murine pregnancy.